2024
DOI: 10.1001/jamainternmed.2023.6538
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy to Treat Snakebites Caused by Bothrops atrox

Érica da Silva Carvalho,
Andrea Renata do Nascimento Souza,
Dessana Francis Chehuan Melo
et al.

Abstract: ImportanceBothrops venom acts almost immediately at the bite site and causes tissue damage.ObjectiveTo investigate the feasibility and explore the safety and efficacy of low-level laser therapy (LLLT) in reducing the local manifestations of B atrox envenomations.Design, Setting, and ParticipantsThis was a double-blind randomized clinical trial conducted at Fundação de Medicina Tropical Doutor Heitor Vieira Dourado, in Manaus, Brazil. A total of 60 adult participants were included from November 2020 to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the literature suggests the potential of PBMT as an alternative therapy for mitigating local effects induced by Bothrops genus snakebites, demonstrating its capacity to attenuate venomrelated damage [4]. Moreover, a recent randomized clinical trial demonstrated that PBMT is feasible and effective in reducing myonecrosis and local inflammatory effects, such as pain and edema, caused by B. atrox envenomations [11]. However, it is important to highlight that existing investigations have not yet provided a comprehensive assessment of how PBMT specifically influences muscle repair following venom exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature suggests the potential of PBMT as an alternative therapy for mitigating local effects induced by Bothrops genus snakebites, demonstrating its capacity to attenuate venomrelated damage [4]. Moreover, a recent randomized clinical trial demonstrated that PBMT is feasible and effective in reducing myonecrosis and local inflammatory effects, such as pain and edema, caused by B. atrox envenomations [11]. However, it is important to highlight that existing investigations have not yet provided a comprehensive assessment of how PBMT specifically influences muscle repair following venom exposure.…”
Section: Introductionmentioning
confidence: 99%